Risk sharing in defined-contribution funded pension systems - Roel Beetsma; Bucciol Alessandro (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper explores the introduction of collective risk-sharing elements in defined contri-bution pension contracts. We consider status-contingent, age-contingent and asset contingent risk-sharing arrangements. All arrangements raise aggregate welfare, as measured by equiva- lent variations. While working individuals hardly benefit or may even lose, retirees experience substantial welfare gains. An increase in the tax deductability of pension contributions can be beneficial for working cohorts, but comes at the cost of a reduction in aggregate welfare due to efficiency losses.
Keywords: H55; I38; C61; 330; funded pensions; risk-sharing; defined contribution; inter-generational welfare; equivalent variation; stochastic simulations